Students’ Perception towards TikTok in Enhancing Their Vocabulary Fluency through Autonomous Learning - Budiartha, Christianus I Wayan Eka; Akmar, Andi Sarah Macenning (Global Expert: Jurnal Bahasa dan Sastra, 2024)
Utilizing social media has been part of most people’s daily lives, especially Generation Z. Social media offers various functions, e.g., socialization, learning, and entertainment. TikTok provides several strategies to improve students’ learning experience regarding English language learning. Those features in social media create a highly motivating environment for students, so it is important to find out how TikTok helps students improve their vocabulary fluency. This study aims to examine students’ perceptions of using TikTok to improve vocabulary fluency through autonomous learning methods and to identify how TikTok, as social media, facilitates EFL students in improving their vocabulary knowledge. The research method for this study is a qualitative approach with a questionnaire and interview. Fifty-six participants were involved in the research, and five attended the focus group discussion. The findings showed that participants believe TikTok is a comfortable tool for vocabulary learning, improving their vocabulary knowledge and vocabulary fluency. From the interview, the participants identified some strategies for learning vocabulary, such as accessing the materials frequently, saving the videos, and utilizing the vocabulary items they learned through TikTok. Keywords: Vocabulary Fluency, TikTok, Autonomous Learning